2013
DOI: 10.1016/j.str.2013.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insights into Recognition of MDC1 by TopBP1 in DNA Replication Checkpoint Control

Abstract: SUMMARY Activation of the DNA replication checkpoint by the ATR kinase requires protein interactions mediated by the ATR activating protein, TopBP1. Accumulation of TopBP1 at stalled replication forks requires the interaction of TopBP1 BRCT5 with the phosphorylated SDT repeats of the adaptor protein MDC1. Here we present the X-ray crystal structures of the tandem BRCT4/5 domains of TopBP1 free and in complex with a MDC1 consensus pSDpT phospho-peptide. TopBP1 BRCT4/5 adopts a variant BRCT-BRCT packing interfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 43 publications
1
30
1
Order By: Relevance
“…MDC1 has also been identified as a potential binding partner of TopBP1 BRCT4/5 and the structure of a consensus MDC1 SDT repeat region (GFIpSDpTDVEEE) bound to TopBP1 BRCT4/5 was solved by X-ray crystallography (Leung et al, 2013). MDC1 interacts with TopBP1 in a manner not observed in other BRCT-peptide structures, with one MDC1 peptide sandwiched between two BRCT4/5 domains.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MDC1 has also been identified as a potential binding partner of TopBP1 BRCT4/5 and the structure of a consensus MDC1 SDT repeat region (GFIpSDpTDVEEE) bound to TopBP1 BRCT4/5 was solved by X-ray crystallography (Leung et al, 2013). MDC1 interacts with TopBP1 in a manner not observed in other BRCT-peptide structures, with one MDC1 peptide sandwiched between two BRCT4/5 domains.…”
Section: Resultsmentioning
confidence: 99%
“…The first potential partner identified for BRCT5 was 53BP1, whose interaction was suggested to mediate recruitment of TopBP1 to sites of DNA double strand breaks (DSBs) during G1 (Cescutti et al, 2010; Yamane et al, 2002). Another DNA double strand break mediator, MDC1, has also been shown to interact with BRCT5, via phosphorylated Ser-Asp-Thr (SDT) repeats in MDC1 (Leung et al, 2013; Wang et al, 2011). However, more recent studies have suggested that, in cells, TopBP1 instead binds to MDC1 via BRCT1 (Blackford et al, 2015; Choi and Yoo, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…We provided a series of experiments to support an interaction between MDC1 and the BRCT5 domain of TopBP1 (Wang et al, 2011). In addition, structural analysis further supported this interaction between the TopBP1 BRCT5 domain and phosphorylated MDC1 (Leung et al, 2013). Interestingly, we found that MDC1 and BLM are, respectively, the major TopBP1 BRCT5 domain-associated proteins in chromatin and soluble fractions (please see Figure 1A in Wang et al, 2013), which was the starting point of our story.…”
mentioning
confidence: 56%
“…40 In human cells, TopBP1 accumulation at stalled forks induced by the replication inhibitor hydroxyurea is mediated by direct interactions between phosphorylated MDC1 and the BRCT5 domain in TopBP1. 41,42 Replication fork restart and post-replicative gap filling mechanisms As mentioned above, ATR activation in response to replication stress leads to stabilization of stalled forks. Two damage tolerance pathways exist to promote fork restart: template switching and translesion synthesis.…”
Section: Topbp1 Is Required For Atr Activationmentioning
confidence: 99%